HER2 expression and markers of phosphoinositide-3-kinase pathway activation define a favorable subgroup of metastatic pulmonary adenocarcinomas. Issue 1 (April 2015) - Reis, H.; Herold, T.; Ting, S.; Worm, K.; Huber, U.; Christoph, D.C.; Eberhardt, W.E.; Kostbade, K.; Kasper, S.; Stamatis, G.; Welter, S.; Darwiche, K.; et al.
Highlights Prospective HER2-analysis in 193 patients with stage III/IV pulmonary adenocarcinoma. HER2- and pAKT-expression correlate with favorable prognosis in stage IV disease. HER2 IHC is not predictive of HER2 amplification or mutation.